1994
DOI: 10.1007/bf00865473
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine growth retardation leads to a permanent nephron deficit in the rat

Abstract: Intrauterine growth retardation (IUGR) was induced in Sprague-Dawley rats by partial artery ligation of one uterine horn in the mother on day 17 of gestation or by feeding the mother a 5% protein diet from day 8 of gestation. The controls were pups of the contralateral uterine horn or pups born to mothers fed a normal (22%) protein diet. The number of nephrons present at birth and the final number of nephrons in 2-week-old rats were counted throughout the entire kidney. The number of nephrons present at birth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
199
5
11

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 339 publications
(238 citation statements)
references
References 25 publications
18
199
5
11
Order By: Relevance
“…In small, long-term studies of individuals of low birthweight, glomerular filtration rate and UAER are normal in early adulthood [27,28]. Many previous studies have described changes in glomerular volume [23,29,30] secondary to a reduction in glomerular number produced by a variety of causes. However, a detailed systematic analysis of kidney morphology in low birthweight animals has not been described previously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In small, long-term studies of individuals of low birthweight, glomerular filtration rate and UAER are normal in early adulthood [27,28]. Many previous studies have described changes in glomerular volume [23,29,30] secondary to a reduction in glomerular number produced by a variety of causes. However, a detailed systematic analysis of kidney morphology in low birthweight animals has not been described previously.…”
Section: Discussionmentioning
confidence: 99%
“…Animals of low birthweight (LBW) induced by protein deprivation in utero have smaller kidneys with lower numbers of glomeruli than animals of normal birthweight (NBW) [3,4]. Although some compensatory hypertrophy of the remaining nephrons occurs, it is likely that the total glomerular filtration surface area remains low.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, maternal protein restriction during pregnancy in rats results in offspring with low birth weight offspring and reduced kidney size and nephron endowment [3][4][5]. It has been postulated that a reduction in nephron endowment acts as a primary renal insult on the kidney, whereby compensatory mechanisms are initiated to maintain normal renal function [6].…”
Section: Introductionmentioning
confidence: 99%
“…A number of experimental and human studies have demonstrated reduced nephron endowment as a result of IUGR, suggesting that a compromised in utero environment impairs nephrogenesis (1)(2)(3). A reduction in nephron number at birth could have long-lasting effects on renal function.…”
mentioning
confidence: 99%